2021
DOI: 10.1021/acsomega.0c05486
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Tetracyanoquinodimethane Derivatives: Enhanced Fluorescence in Solutions and Unprecedented Cation Recognition in the Solid State

Abstract: Tetracyanoquinodimethane (TCNQ) is known to react with various amines to generate substituted TCNQ derivatives with remarkable optical and nonlinear optical characteristics. The choice of amine plays a crucial role in the outcome of molecular material attributes. Especially, mono/di-substituted TCNQ’s possessing strong fluorescence in solutions than solids are deficient. Furthermore, cation recognition in the solid-state TCNQ derivatives is yet undetermined. In this article, we present solution-enhanced fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Consequently, from the above study we can infer that mono-substituted derivatives [1], [4] showed similar features mainly due to conjugation, and di-substituted (displaying large dipole moments) [2], [3] and [7] exhibited alike attributes primarily owing to zwitterionic characteristic. [33][34]39,44] [2], [3] and [7] demonstrated fluorescence enhancement in solids (Figure 6, Table S5-S9) as well, feature noticed in certain previously reported DADQ's, due to the strong zwitterion nature in di-substituted TCNQ's leading to restricted intramolecular motion in solid/aggregated state. [47][48] Nevertheless, [1] and [4] possess extended conjugation in their structural arrangement leading to the enhancement of fluorescence in solutions.…”
Section: Optical Propertiessupporting
confidence: 62%
See 4 more Smart Citations
“…Consequently, from the above study we can infer that mono-substituted derivatives [1], [4] showed similar features mainly due to conjugation, and di-substituted (displaying large dipole moments) [2], [3] and [7] exhibited alike attributes primarily owing to zwitterionic characteristic. [33][34]39,44] [2], [3] and [7] demonstrated fluorescence enhancement in solids (Figure 6, Table S5-S9) as well, feature noticed in certain previously reported DADQ's, due to the strong zwitterion nature in di-substituted TCNQ's leading to restricted intramolecular motion in solid/aggregated state. [47][48] Nevertheless, [1] and [4] possess extended conjugation in their structural arrangement leading to the enhancement of fluorescence in solutions.…”
Section: Optical Propertiessupporting
confidence: 62%
“…A minimal blue shift (∼12 nm) in the λ max emission (Table S4) of [ 7 ] in MeOH, EtOH when compared to the latter, could be due to the restricted non‐radiative decay of the excited states owing to its stabilization. One of our very recently reported BAPMDQ and APMTQ; [44] bearing 4‐(4‐aminophenyl) morpholin‐3‐one (APM) revealed similar blue shift in DMSO and DMF. Consequently, from the above study we can infer that mono‐substituted derivatives [ 1 ], [ 4 ] showed similar features mainly due to conjugation, and di‐substituted (displaying large dipole moments) [ 2 ], [ 3 ] and [ 7 ] exhibited alike attributes primarily owing to zwitterionic characteristic [33–34,39,44] .…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations